Robust electrochemical transducer using conductive polymer (PEDOT : PSS) composite for glucose biosensor application - Abdelmohsen, Benoudjit (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Poly(3,4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS) is widely used in the fabrication of capacitors, solar cells, transistors, and especially biosensors. Stability and adhesion of a PEDOT:PSS transducer in liquid media are major problems in the fabrication of robust sensors owing to the easy disintegration of PEDOT:PSS from electrode surfaces. In this study, the effect of using electropolymerization deposition (EPD) and drop-casting (DC) on the stability and adhesion of the PEDOT:PSS transducer were studied. Furthermore, the effect of PEDOT:PSS ratio on the stability of the transducer in liquid media was investigated and a glucose biosensor was synthesized and characterized based on an electropolymerized PEDOT:PSS transducer. The galvanostatic mode was employed using a potentiostat/galvanostat at 100 µA and 400 mV for electropolymerization deposition of EDOT and PSS to PEDOT:PSS on electrode surfaces. A PEDOT:PSS transducer deposited on a flat platinum electrode (FPtE) and soaked in phosphate-buffered saline (PBS) solution for more than 15 days showed long-term stability, retaining almost 99% of its original activity. For further confirmation of the robustness of a PEDOT:PSS transducer synthesized by EPD, a commercially available aqueous dispersion of PEDOT:PSS was deposited by DC on FPtE as transducer for comparison purposes. The stability and adhesion of PEDOT:PSS deposited via EPD and DC were tested in dynamic liquid media. A PEDOT:PSS transducer fabricated using EPD maintained almost 99.9% of its original activity after a water-flow test; in contrast, the one fabricated using DC lost 95% of its original activity. Field emission scanning electron microscope (FESEM) results revealed that the structure of the PEDOT:PSS transducer fabricated using EPD remains intact on electrode surfaces after a water-flow test. Moreover, with EPD, the PEDOT:PSS ratio did not have any effect on the stability of a PEDOT:PSS transducer. Finally, a glucose biosensor with a PEDOT:PSS transducer was successfully fabricated, and the sensitivity and efficiency were 285.2 nA/mM and 17.68 µA/mM cm2, respectively. The results suggest that using EPD to synthesize a PEDOT:PSS transducer could enhance the robustness of the transducer in liquid media, thereby providing a future platform for electrochemical biosensors with high sensitivity and stability, especially for dynamic liquid media use.